2016
DOI: 10.1109/tdei.2015.005374
|View full text |Cite
|
Sign up to set email alerts
|

Flashover performance of ice-covered post insulators with booster sheds using experiments and partial arc modeling

Abstract: The main objective of this paper is to present a new analysis, founded on partial arc activities, for evaluating the flashover performance of EHV post station insulators equipped with booster shed (BS) under heavy icing conditions. Based on observations from ordinary and high-speed cameras, novel discussions on partial arc characteristics, ice-free leakage distances, and flashover arc path were presented. Moreover, innovative axisymmetric simulations of partial arcs were implemented by using COMSOL Multiphysic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…In order to explain the effects of the rain intensity, the finite element method is applied to study the electric field distributions of the test specimens under rain conditions in the Ansoft software. The simulation model is shown in Figure 6a, and the simulation parameters are obtained from [22][23][24], the relative permittivity of the ZnO varistor, silicone rubber sheds and epoxy resin are 800, 3 and 6 respectively. The metal fitting is set to be ideal conductor.…”
Section: 2effects Of Rain Intensitymentioning
confidence: 99%
“…In order to explain the effects of the rain intensity, the finite element method is applied to study the electric field distributions of the test specimens under rain conditions in the Ansoft software. The simulation model is shown in Figure 6a, and the simulation parameters are obtained from [22][23][24], the relative permittivity of the ZnO varistor, silicone rubber sheds and epoxy resin are 800, 3 and 6 respectively. The metal fitting is set to be ideal conductor.…”
Section: 2effects Of Rain Intensitymentioning
confidence: 99%
“…S.M. Ale-Emran proposed using a high-speed camera to observe the characteristics of the partial arc on the ice-covered post insulator with booster sheds, and simulated the electric field distribution of the insulator when a partial arc occurred based on the finite element method [16]. However, the simulation analysis was carried out in two-dimensional axisymmetric state, which is different from the three-dimensional electric field of insulators after the partial arc occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…It is proved that the variations of sheds configures can affect the number and length of the air gaps on the iced insulators, and the air gaps can impact the insulators' icing flashover performance [16]. Experimental studies were carried out, and the booster sheds were found to be an effective way to improve the icing flashover performance of composite insulators [17]. The booster sheds effects on the flashover performance of ice-covered post insulators have been studied using experimental and simulation methods [18].…”
Section: Introductionmentioning
confidence: 99%